2022
DOI: 10.3390/nu14132571
|View full text |Cite
|
Sign up to set email alerts
|

Food Environments and Their Influence on Food Choices: A Case Study in Informal Settlements in Nairobi, Kenya

Abstract: The food environments that people have access to shape their food choices. The purpose of this study was to use mixed methods to characterize the external food environment in informal settlements in Nairobi, Kenya and to examine the individual factors that influence the way in which women interact with those environments to make food choices. We used a combination of food environment assessments (vendor mapping, collection of food prices, food quality assessments) and five focus group discussions with women (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 36 publications
3
5
0
Order By: Relevance
“…In all the locations we investigated, there were poor average dietary diversity scores, indicating diets that are likely low in micronutrients. Similar to our study, several studies have observed that the poorest communities are at the highest risk of insufficient micronutrient intake due to low consumption of vegetables and fruits, as well as animal‐sourced foods and other sources of protein 26–30 . Sub‐optimal diets predispose low‐income urban populations to undernutrition, poor micronutrient status and, when combined with shifts towards urban lifestyles, NCDs.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…In all the locations we investigated, there were poor average dietary diversity scores, indicating diets that are likely low in micronutrients. Similar to our study, several studies have observed that the poorest communities are at the highest risk of insufficient micronutrient intake due to low consumption of vegetables and fruits, as well as animal‐sourced foods and other sources of protein 26–30 . Sub‐optimal diets predispose low‐income urban populations to undernutrition, poor micronutrient status and, when combined with shifts towards urban lifestyles, NCDs.…”
Section: Discussionsupporting
confidence: 86%
“…In Nairobi, convenience was identified as a key factor influencing food choice, confirming previous observations by Downs et al 26 We did not collect additional information on the issues around convenience, such as perceived cost savings, ease of access to street vendors versus open‐air markets and use of fuel. Nevertheless, for Nairobi, improving the quality of food from vendors and retailers or kiosks would be a key strategy so that convenient food is also healthful and available within short walking distances.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations